Analytical Hierarchy Process Method in the Decision Support System for Non-Cash Food Assistance Recipients - Fajria, Rahmat; Rahmawati, Sri; Jamhur, Annisak Izzaty (Universitas Putra Indonesia YPTK Padang, 2025)
Non-Cash Food Assistance is food assistance provided by the government to the poor. The assistance aims to reduce the burden of expenditure and provide better nutritional intake to the poor, the research site still makes decisions manually or checks the documents of the applicant for assistance and matches them with the criteria one by one without using an accurate system, This method is very time consuming and this results in errors so that assistance is less targeted and considered not optimal. In finding and determining decisions based on technology, many methods can be used, one of which is the Analytic Hierarchy Process (AHP) method. This research will be built using a decision support system using the Analytical Hierarchy Process (AHP) method. The AHP method is a method that is widely used in cases of criteria weighting and determining the priority of each criterion. The calculation results show that the CR value < 0.1 , so the consistency ratio is considered acceptable. This study has succeeded in meeting the need for information related to the selection of Non-Cash Food Assistance recipients, and has helped in solving problems related to the process of selecting recipients of the assistance